The Use of the Word Nego in Facebook Forum of Online Trading: a Sociolinguistic Review - Santosa, Joko; Setiawaty, Rani; Wahyudi, Agus Budi; Sabardila, Atiqa; Andres, Darwin M; Tiyo, Anggara (Universitas Muria Kudus, 2022)
Tujuan penelitian ini adalah mendeskripsikan penggunan (1) bentuk dan referensi kata nego; dan (2) fungsi penggunaan kata nego dalam forum facebook jual beli online. Data yang dideskripsikan dalam penelitian ini adalah pada penggunaan kata nego dalam forum facebook jual beli online. Metode pengumpulan data yang digunakan dalam penelitian ini adalah metode dokumentasi. Adapun, teknik analisis data yang digunakan adalah analisis isi dengan model Milles Huberman, yakni dimulai dari pengumpulan data, reduksi data atau pengklasifikasian, analisis, hingga penarikan kesimpulan. Berdasarkan hasil temuan dan pembahasan, disimpulkan pertama penggunaan kata nego meliputi nego bensin, nego pertamax, nego sak dadine, nego sampe jadi, nego sampe deal, nego tipis, nego wajar, nego kalem, nego alus, nego ngawur, nego ukur-ukur, nego loos, nego lhas-lhes, nego kedik, dan nego sitik. Beberapa kata nego tersebut mempunyai rujukan harga benda, tujuan akhir, sifat benda, proses atau aktivitas tawar menawar, dan jumlah harga. Kedua, penggunaan kata nego oleh penutur/penjual berfungsi untuk (1) menekankan pada calon pembeli terkait harga yang akan ditawar; (2) memaksimalkan keuntungan bagi calon pembeli, (3) memaksimalkan keuntungan bagi kedua belah pihak sehingga salah satu pihak tidak mengalami kerugian. The purpose of this study is to describe the use of (1) forms and references of the word nego; and (2) the function of using the word nego in the online buying and selling facebook forum. The data described in this study is on the use of the word nego in the online buying and selling facebook forum. The data collection method used in this research is the documentation method. Meanwhile, the data analysis technique used is content analysis with the Milles Huberman model, starting from data collection, data reduction or classification, analysis, to drawing conclusions. Based on the findings and discussion, it is concluded that the first use of the word nego includes negotiating gasoline, negotiating pertamax, negotiating sak dadine, negotiating until finished, negotiating until a deal, negotiating thin, negotiating fair, negotiating calm, negotiating alus, nego alon, nego banter, negotiating with beautifully, negotiating inconsequential, negotiating measures, nego loos, nego lhas- lhes, nego kedik, nego sitik, nego akeh sak pol e, and nego gedhen. Some of these negotiable words have a reference to the price of the object, the final destination, the nature of the object, the process or activity of bargaining, and the amount of the price. Second, the use of the nego, forms, function, buying and selling facebook forum word nego by speakers/sellers serves to (1) emphasize on potential buyers regarding the price to be offered; (2) maximize profits for potential buyers, (3) maximize profits for both parties so that one party does not experience a loss.